2006
DOI: 10.1002/cncr.22084
|View full text |Cite
|
Sign up to set email alerts
|

Should we screen for bladder cancer in a high‐risk population?

Abstract: BACKGROUND.The U.S. Food and Drug Administration recently approved screening high‐risk patients for bladder cancer using urine‐based markers. The cost and life‐years saved associated with bladder cancer screening were evaluated.METHODS.A Markov model was created to estimate cumulative cancer‐related costs and efficacy of screening (vs. no screening) of a high‐risk population for bladder cancer using a urine‐based tumor marker over a 5‐year period. Assumptions were based on literature review of survival and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 38 publications
1
58
0
3
Order By: Relevance
“…These studies have evaluated the treatment of patients with transitional cell cancer, 39,40 analyzed options for screening for bladder cancer, 41,42 or quantified costs associated with bladder cancer follow-up and complications. 37,43,44 Although those results are not directly comparable with our analysis, these and other 45,46 studies reported cost estimates that were similar to the estimates in our model, suggesting that our single institution's cost estimates may be broadly applicable to other settings.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have evaluated the treatment of patients with transitional cell cancer, 39,40 analyzed options for screening for bladder cancer, 41,42 or quantified costs associated with bladder cancer follow-up and complications. 37,43,44 Although those results are not directly comparable with our analysis, these and other 45,46 studies reported cost estimates that were similar to the estimates in our model, suggesting that our single institution's cost estimates may be broadly applicable to other settings.…”
Section: Discussionmentioning
confidence: 99%
“…Such considerations are directly dependent on the incidence of the disease as well as on the sensitivity and specificity of the marker, in addition to the overall costs of each test. 7 Lotan and colleagues 6 reported that screening of all men aged 55 years or older was significantly more costly on a per-cancer basis than screening only in a highrisk group (more than US$400 000 v. $3130). Svatek and colleagues 7 suggest that marker screening of a high-risk group could be cost effective, although additional studies in an asymptomatic cohort are required before screening of a general population is recommended.…”
Section: Urovysionmentioning
confidence: 99%
“…Based on the care pathway described in Chapter 2, the model structure was developed following consultation with clinicians and taking into consideration the approaches adopted by the existing economic evaluations 153,158,[175][176][177][178][179][180] identified from the literature. The approach attempts to model patients passing through the whole sequence of care and determine the overall impact on costs and the clinical consequences.…”
Section: Economic Model For Initial Diagnosis and Follow-up Of Bladdementioning
confidence: 99%